Antonio Gramsci between (International / National) Social Struggles and Intellectual Contexts - Gómez, Sebastián (2023)
After its first publication in Italy (Fresu 2019) and then in Brazil(Fresu 2020), Gianni Fresu’s Antonio Gramsci, an Intellectual Biographyhas now been published in English in (Fresu 2022). In the contextof the Marx and Marx studies renaissance, Palgrave Macmillan haspromoted new research in the series Marx, Engels and Marxism. Inthis series, Fresu reflects upon one of the most important andoriginal Marxists of the twentieth century, Antonio Gramsci (1891-1937). His book brings together the results of a long investigationof the life and thought of Gramsci that started in 2005 with Ildiavolo nell’ampolla: Antonio Gramsci, gli intellettuali e il partito. Sincethen, Fresu has continued his work in Italy as a researcher inpolitical philosophy at the University of Cagliari, but also in Brazilwhere he is a professor of political philosophy at the FederalUniversity of Uberlandia. With a wide knowledge of old and newworldwide studies of Gramsci, Fresu links two dimensions in hisstudy of Gramsci: his life and his thought.